2013
DOI: 10.1017/s0007114513000779
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast high in whey protein or carbohydrates improves coping with workload in healthy subjects

Abstract: Dietary components may affect brain function and influence behaviour by inducing the synthesis of neurotransmitters. The aim of the present study was to examine the influence of consumption of a whey protein-containing breakfast drink v. a carbohydrate drink v. control on subjective and physiological responses to mental workload in simulated work. In a randomised cross-over design, ten healthy subjects (seven women, median age 26 years, median BMI 23 kg/m 2 ) participated in a single-blinded, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Interestingly, a marginal trend of CHO-related facilitation was found for the overall mood construct calculated for each individual study. It should be noted that some of the effect sizes included in this construct originated from studies that selectively reported only CHO-mood associations that were statistically significant (e.g., Lieberman et al, 2002;Sihvola et al, 2013). To illustrate, although Lieberman et al (2002) used the full version of the POMS (six subscales), they only provided data on Confusion/Bewilderment and Vigor/Activity, while no data were available for the remaining four subscales of the POMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a marginal trend of CHO-related facilitation was found for the overall mood construct calculated for each individual study. It should be noted that some of the effect sizes included in this construct originated from studies that selectively reported only CHO-mood associations that were statistically significant (e.g., Lieberman et al, 2002;Sihvola et al, 2013). To illustrate, although Lieberman et al (2002) used the full version of the POMS (six subscales), they only provided data on Confusion/Bewilderment and Vigor/Activity, while no data were available for the remaining four subscales of the POMS.…”
Section: Discussionmentioning
confidence: 99%
“…For the 61+ time window, eight studies were found to be relevant. However, Sihvola et al (2013) had to be excluded as it was found to be an outlier (z = 2.55) leaving seven studies in the analysis. No effects of CHO on alertness were found for this time window (p = .343).…”
Section: Bond-lader Vasmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is also limited by not including a mental stress alone condition or an exercise alone condition to investigate the effects of CHO ingestion and make comparisons between such treatments to further investigate treatment effects. However, previous studies have reported that CHO intake can improve cardiovascular responses to both psychological [31] and physical stress [3,24,26,27]. The purpose of this study was to investigate the effects of CHO ingestion on DCS exposure with the intention of providing justification for future research to continue to investigate nutritional interventions on endocrine and metabolic responses to DCS challenges.…”
mentioning
confidence: 99%
“…At the outset, we acknowledge that much of our focus here is on depression. This is largely because depression has received the lion’s share of international research attention as it relates to some of the nutritional and environmental variables; however, it should be understood that these discussions are of relevance to diverse topics ranging from reductions in violent behavior [54] to overall positive mental outlook in those who are otherwise well-adjusted [55,56]. …”
Section: Introductionmentioning
confidence: 99%